PHARMACOECONOMIC ANALYSIS OF MEDICINES USED IN THE TREATMENT OF ITSENKO-CUSHING'S DISEASE (Conferencea, 2022)
Costs for the treatment of Itsenko-Cushing's syndrome in the Republic of Uzbekistan were calculated and studied on the basis of data from the Republican Specialized Scientific and Practical Endocrinological Medical Center.